BUILDING INCLUSIVE COMMUNITIES: LEARNING FROM THE WORLD. (11th November 2018) - Bonner, A; Mutchler, J E
Abstract: As countries around the world are rapidly aging, cities and towns are finding new ways to harness the unprecedented opportunity and challenge of this newfound human longevity. The World Health Organization's (WHO) Age-Friendly Cities model is an international framework to help cities assess and improve features of their communities that promote participation, health, and quality of life for older adults of all abilities, including adults living with dementia. This session brings together five international scholars who are focused on building these age-friendly communities to share their learnings and experiences. They will present their work and spark discussion about the ways they have managed to build communities that are inclusive of all older adults—including those with physical disabilities and cognitive impairment. Presenters from the United Kingdom, Ireland, Canada, China, and the United States will provide overviews of their approaches to building age-friendly environments, highlighting challenges and successes in ensuring the inclusivity of these communities extends to persons with disabilities and those living with dementia. In addition to international perspectives, these presenters come from a range of disciplines including urban planning, architecture, demography, and disability studies. This session will also provide an opportunity for open dialogue among presenters and attendees to share the diverse and creative ways they have addressed age-friendliness in their countries and communities. We have much to learn from one another about creating communities that promote inclusion, health, and quality of life for aging across the lifespan.